Pulse Wave Velocity in Korean American Men and Women - Logan, Jeongok G. (2013)
Arterial stiffness is an important clinical marker of cardiovascular diseases. Although many studies have been conducted on different racial groups, less is known about arterial stiffness in Asian Americans. Korean Americans constitute the fifth largest subgroup in the Asian American population and reportedly have a noticeably high prevalence of hypertension. The aims of this study were to assess arterial stiffness and blood pressure and to examine the effect of age and gender on arterial stiffness and blood pressure in 102 Korean American men and women aged 21 to 60 years. The values of arterial stiffness for Korean Americans in this study were compared to published reference values for other racial and ethnic groups. Arterial stiffness was measured by carotid-femoral pulse wave velocity, which is the gold standard for determining arterial stiffness. Findings indicated that aging was an important determinant of arterial stiffness, which increased linearly with age. Although there was no gender difference observed in arterial stiffness, the effect of age on arterial stiffness was greater in women than in men. After adjusting for covariates including age, body mass index, and smoking, multiple regression models showed that arterial stiffness and gender were significant predictors of systolic and diastolic blood pressure. The comparisons of these findings to those from several other studies that used the same method to measure arterial stiffness showed that Korean Americans may have levels of arterial stiffness that are similar to or slightly higher than those of other racial groups. Considering that arterial stiffness is an independent predictor of future development of hypertension, more studies are required to examine cardiovascular risk of this understudied group.